Reliability-Oriented Decoding Strategy for LDPC Codes-Based D-JSCC System - Lyu, Yibo; Hong, Shaohua; Wang, Lin; Xiong, Zixiang (IEEE communications letters, 2017)
In this letter, a reliability oriented decoding strategy (RODS) for low density parity check codes-based distributed joint source and channel coding system is proposed. During each local decoding iteration, the reliability of each variable node is evaluated based on the sign of received log-likelihood ratios (LLRs) and its oscillation situation. Then, by employing reliability-oriented updating operation, the negative influence of those inaccurate messages is suppressed. Moreover, extra operations are performed on a group of most unreliable source nodes so that more accurate posteriori LLRs can be obtained. During global iteration, offset operation is performed to reduce error propagation. The simulation results illustrate that the proposed RODS outperforms other decoding algorithms at the aspects of error correction performance and convergence speed, especially when the correlation between distributed sources is low.